PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN PEGAWAI TERHADAP KUALITAS PELAYANAN PADA BADAN KEPEGAWAIAN DAERAH PROVINSI LAMPUNG - eka ubaya; Emilia Tri Hastuti (e-JKPP, 2019)
The problems in this study are: (1) Does the leadership style affect the quality of service in the Lampung Provincial Regional Personnel Agency, (2) Does the discipline of employees affect the quality of service in the Lampung Province Regional Civil Service Agency, (3) Does the leadership style and employee discipline influence on the quality of service at the Lampung Provincial Regional Personnel Agency.This study uses an explanatory design, an explanatory survey is an investigation of causality by basing on observations of the effects that occur, namely conducting research by taking a sample from the population using a questionnaire as a data collection tool, by analyzing the influence of leadership style variables and employee discipline as independent variables (independent variable), towards service quality as the dependent variable.The results showed that there was a significant influence of both leadership style and employee discipline on the quality of service at the Lampung Provincial Regional Civil Service Agency, the greatest influence of the leadership style variable and employee discipline was the Leadership Style variable. Based on the results of the study, that the contribution of leadership style variables and employee discipline to service quality, is in the quite good category but not optimal. This happens because there is no optimal application of regulations, so that employees have not been motivated in carrying out their duties that have not yet impacted the quality of service at the Lampung Provincial Civil Service Agency.